ANALYSIS OF THE EFFECTIVENESS OF IT COMPANIES: A COMPARATIVE APPROACH - HORDOPOLOV, Volodymyr; BONDAR, Dmytro (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article focuses on the need to combine financial and non-financial indicators as a prerequisite for an objective assessment of the performance and competitiveness of IT businesses. Traditional financial indicators, such as profitability, liquidity, and return on investment, allow only for the assessment of past performance, but do not reveal the resilience of the business to change or its strategic development prospects. Instead, non-financial information — customer satisfaction, staff qualifications, innovation activity, ESG indicators — is becoming increasingly important for investors, partners and regulators.  Based on open analytical sources, a comparative analysis of five leading IT companies in Ukraine (EPAM Systems Ukraine, SoftServe, Intellias, Luxoft Ukraine, N-iX) was conducted, taking into account their size, specialisation and organisational structure, level of innovation, profitability, staff satisfaction and other indicators. For this purpose, a method of integrated performance assessment based on weighted coefficients was used, which includes both financial and non-financial indicators. It was shown that non-financial factors, in particular the level of innovation, ESG strategies and HR policies, are crucial for the long-term development of companies. It was determined that the most balanced results are achieved by companies that combine high profitability with a strong corporate culture. The paper also provides practical recommendations for improving the efficiency of IT companies, including the introduction of non-financial metrics into the management system, the development of an innovative environment, the strengthening of the HR brand, and the systematic use of benchmarking tools. It is argued that the systematic use of a comparative approach contributes to the strategic development of the IT sector, the formation of industry standards, and the enhancement of companies' investment attractiveness.
Keywords: IT companies; efficiency; comparative analysis; financial indicators; non-financial information; innovation; integral index